Community involvement in out of hospital cardiac arrest: A cross-sectional study assessing cardiopulmonary resuscitation awareness and barriers among the Lebanese youth. Issue 43 (October 2016) - Shams, Ali; Raad, Mohamad; Chams, Nour; Chams, Sana; Bachir, Rana; El Sayed, Mazen J.
Abstract : Abstract: Out of hospital cardiac arrest (OHCA) is a leading cause of death worldwide. Developing countries including Lebanon report low survival rates and poor neurologic outcomes in affected victims. Community involvement through early recognition and bystander cardiopulmonary resuscitation (CPR) can improve OHCA survival. This study assesses knowledge and attitude of university students in Lebanon and identifies potential barriers and facilitators to learning and performing CPR. A cross-sectional survey was administered to university students. The questionnaire included questions regarding the following data elements: demographics, knowledge, and awareness about sudden cardiac arrest, CPR, automated external defibrillator (AED) use, prior CPR and AED training, ability to perform CPR or use AED, barriers to performing/learning CPR/AED, and preferred location for attending CPR/AED courses. Descriptive analysis followed by multivariate analysis was carried out to identify predictors and barriers to learning and performing CPR. A total of 948 students completed the survey. Participants' mean age was 20.1 (±2.1) years with 53.1% women. Less than half of participants (42.9%) were able to identify all the presenting signs of cardiac arrest. Only 33.7% of participants felt able to perform CPR when witnessing a cardiac arrest. Fewer participants (20.3%) reported receiving previous CPR training. Several perceived barriers to learning and performing CPR were also reported. Significant predictors of willingness to perform CPR when faced with a cardiac arrest were: earning higher income, previous CPR training and feeling confident in one's ability to apply an AED, or perform CPR. Lacking enough expertise in performing CPR was a significant barrier to willingness to perform CPR. University students in Lebanon are familiar with the symptoms of cardiac arrest, however, they are not well trained in CPR and lack confidence to perform it. The attitude towards the importance of bystander CPR and the need to learn CPR is very positive. Interventions should focus on public awareness campaigns regarding the importance of initiating bystander CPR while activating emergency medical services (EMS) and on making CPR training more available.